Strategy moves : 14 complete attack and defense strategies for competitive advantage - Vasconcellos e Sá, Jorge A. De (Financial Times Prentice Hall, 2005)
This book will become the bible of a bible for the field of business strategy for many years to come. An invaluable playbook of strategic moves for managers, marketers and entrepreneurs, covering all 14 known attacking and defending strategies, and backed up by over three hundred international examples. Backed up by copious examples from industry: more than 300 examples in the text, and a unique chapter case study on how Japanese auto firms conquered the US market using a combination of various moves covered in the book. Almost twenty years after the appearance of Al Ries's groundbreaking Marketing Warfare, the time is right to bring the practitioners up to date with the thinking and show them how to use it. A Complete manual. The book is built around the 14 strategic moves. It shows you what move to use, how to use it, and when. Like a book of chess moves for business. Positioning and Marketing Warfare are two of the most successful books ever published in marketing/business strategy, and Strategy Plays clearly falls in that space. Will prominently feature endorsements from Kotler and from Ries.